Pycnoscelus surinamensis Endosymbiont Bacteria: Identification and its Amylase Characteristic - Ni'matuzahroh; Fatimah; Sholikah; Ayu Tri Wahyuni; Tri Nurhariyati; Mochammad Affandi; Agus Supriyanto; Almando Geraldi; Tini Surtiningsih; Brigita Nur Diyan Agustiana; Dela Dwi Alawiyah; Ana Mariatul Khiftiyah; Silvia Kurnia Sari (Universitas Airlangga, 2023)
The amylase is an enzyme that widely used in industry. In this research, amylase was isolated from endosymbiont bacteria (EKA 4) of cockroach Pycnoscelus surinamensis from household garbage dump Surabaya. This research aims to identify bacteria EKA 4, produce and characterize amylase from it at various temperature, pH and effect of metal ions. Amylase screening assay was done by imoculating the isolate into medium contain 2% of starch then incubated for 24 hours. Detection of amylase was done qualitatively by measured presence of halozone and quantitatively using DNS method. 16S rRNA analysis found that bacteria EKA 4 has similarity to Bacillus subtilis with 100% of percent identity. Result showed that optimum activity of amylase from B. subtilis were at 40°C, pH 6 and could use ion CaCl2 as a cofactor in a reaction. Thus, utilization of amylase from endosymbiont P. surinamensis could be as an alternative source in big industries.